(untitled) (Eurasian Research Bulletin, 2022)
This article covers the fact that the Internet network is an effective tool for human communication, which causes the intensity of human activity. It is also revealed that the increase in the number of users of information published on the Internet in all countries of the world and the sharp increase in the social need for internet sites has caused the virtual information space.